Drawing Maps for Research in Creative Writing through A/r/tography - Chrysogonus Siddha Malilang (Journal of Urban Society's Arts, 2017)
The return of Creative Writing to the academia was intended as an answer to rigid approaches employed in the nineteenth century’s teaching of English Literature. This comeback has since brought back a new perspective in seeing body of literature as a living body but at the same time also introduced clash between dominating research paradigm in the academia. The writers who were hired to teach creative writing tended to prioritise their creative practice, while the general consensus in academia called for more theoretical-oriented research. In order to compromise, the practice-based research method was born.  Despite various justifications that creative process is the same as research inquiry, the heavier emphasis on creative works in this method still invites criticism, such as the lack of research rigour (Biggs & Büchler, 2007). New framework to balance and bridge practice and research rigour is thus needed – especially one that can accommodate the non-linear thinking trajectories in creative practices. Due to the possible non-linearity, the new research platform should not follow the reigning ‘arborescent scheme’ in the academic research tradition, but incorporate the concept of Deleuzian rhizome.  A/r/tography – developed based on the premise of art and art creation as a rhizomatic process / activity – is proposed as one of the potential practices for creative writing research. The non-linear view of a/r/tography towards arts practices suggests a rhizomatic role in the mapping of creative writing process. As it addresses and accommodates multiplicities, a/r/tography also facilitates non-native English speakers to conduct and map his journey in art creation and research inquiry. Author’s project of writing a collection of bilingual poems based on classical Javanese song cycle – Sekar Macapat – is presented to illustrate the claim.